Pengaruh Terapi Dzikir Terhadap Kualitas Tidur Pasien Hospitalisasi Di Rs Islam Â SakinahMojokerto - Sudiyanto, Henry; Wahid, Abdul (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractSleep quality of hospitalized patients (I lospitalization) in Islamic I lospital Sakinah Mojokerto decreased. Poor sleep quality can be treated with non-pharmacological therapy, one of them with dhikr therapy. This study aims lo determine the effect of dhikr therapy on sleep quality of hospitalization patients. The type of research used is quasi-experimental research and used Pretest-Postrest Control Group Design method. The sample used 30 respondents, 15 treatment groups and 15 control groups. The sampling technique used in this study is Consecutive Sampling. The measuring tool used is the PSQI (Pittsburgh Sleep Quality Index) questionnaire. Based on the calculation of Paired Sample Test test p value=0,000 which means there is improvement of sleep quality in the treatment group, whereas p = 0.061 in the control groupwhich means no improvement in sleep quality. Result of Independent Samples Test obtained p = 0,00 l which means there is influence dzikir therapy on sleep quality or hospitalization patient in Sakinah I lospital of Mojokerto. Based on the results of research dzikir therapy conducted for 15 minutes before bed for 3 consecutive days in March 2017 can improve the sleep quality of hospitalization patients, so this research is expected as an input to form a team of spiritual guidance to hospitalization patients with poor sleep quality.Keywords: Sleep quality, dhikr therapy, hospitalization patients